THE INFLUENCE OF LEARNING STYLES AND SCHOOL ENVIRONMENT ON LEARNING MOTIVATION AND ITS IMPLICATIONS ON STUDENT LEARNING OUTCOMES IN ECONOMICS SUBJECTS: (Survey on Students of Grade X and XI Social Sciences Program at SMA Negeri 8 Tasikmalaya in the 2022/2023 Academic Year) - Setiawan, Vito Ari; Gumilar, Gugum (Transpublika Publisher, 2023)
This study aims to determine the influence of learning styles and the school environment on learning motivation and its implications for learning outcomes. The study adopts a quantitative survey research method with an explanatory survey research design. The population for this study comprises X and XI social studies students of SMA Negeri 8 Tasikmalaya in the 2022/2023 academic year, totaling 427 individuals. The sampling technique used is Proportional Random Sampling, resulting in a sample size of 207 respondents. Data is collected through questionnaires, and the data analysis technique employed is Path Analysis or path analysis. Based on the results of data processing, it is found that learning style does not have a significant effect on learning motivation (with a significance value of 0.218). On the other hand, the school environment significantly influences learning motivation (with a significance value of 0.002). Moreover, learning styles do not significantly impact learning outcomes (with a significance value of 0.323), whereas the school environment significantly affects learning outcomes (with a significance value of 0.006). Additionally, learning motivation significantly influences learning outcomes (with a significance value of 0.001). Furthermore, the study reveals that learning styles do not have a significant effect on learning outcomes through learning motivation, as indicated by the t-count value of 0.969. However, the school environment significantly influences learning outcomes through learning motivation, with a t-statistic value of 2.149.